Risk of Recurrent Venous Thromboembolism in Selected Subgroups of Men: A Danish Nationwide Cohort Study - Albertsen, Ida Ehlers; Konstantinides, Stavros V.; Piazza, Gregory; Goldhaber, Samuel Z.; Larsen, Torben Bjerregaard; Søgaard, Mette; Nielsen, Peter Brønnum (TH Open, 2022)
Background Although men are considered at high risk for recurrent venous thromboembolism (VTE), sex-specific data on prognostic factors are lacking. We estimated the cumulative recurrence risks associated with clinical characteristics and comorbidities known or suspected to be associated with the development of VTE recurrence: major surgery, trauma, history of cancer, rheumatic disorder, ischemic heart disease, congestive heart failure, chronic obstructive pulmonary disease, diabetes, chronic renal disease, varicose veins, alcohol-related diseases, and arterial hypertension.Methods We linked nationwide Danish health registries to identify all incident VTE in- and outpatients in men from 2008 through 2018. Recurrent VTE risk 2 years after anticoagulant discontinuation was calculated using the Aalen-Johansen estimator, stratified by age above/below 50 years.Results The study included 13,932 men with VTE, of whom 21% (n = 2,898) were aged <50 years. For men aged <50 years with at least one of the clinical characteristics, 2-year recurrence risk ranged from 6% (major surgery) to 16% (history of cancer). For men ≥50 years with at least one of the characteristics, recurrence risk ranged from 7% (major surgery) to 12% (ischemic heart disease, chronic obstructive pulmonary disease, and chronic renal disease). Men aged <50 and ≥50 years without the clinical characteristics all had a recurrence risk of 10%.Discussion We demonstrated a 2-year recurrence risk of at least 6%, regardless of age category and disease status, in this nationwide cohort of men with VTE. The recurrence risk must be balanced against bleeding risk. However, the high recurrence risk across all subgroups might ultimately lead to greater emphasis on male sex in future guidelines focusing on optimized secondary VTE prevention.
Keywords: venous thromboembolism; recurrence; sex; men; anticoagulation; treatment